THE EFFECT OF WORD SEARCH PUZZLE TEACHING MEDIA TO THE VOCABULARY MASTERY OF GRADE SEVEN - Doris Yolanda Saragih; Firinta Togatorop (Dharmas Education Journal (DE_Journal), 2024)
This research examined about coherence and unity of the students’ writing descriptive paragraph at Grade VIII in SMP Negeri 2 Pematangsiantar. The problem of the research is : How are the students’ coherence and unity in writing descriptive paragraph at grade VIII of SMP Negeri Pematangsiantar. This research was designed as qualitative research in which the data was analyzed inductively. The researcher used one class to analyze their writing. The data was taken from writing essay from the students in Eight-9 class. The students are grade VIII at SMP Negeri 2 Pematangsiantar as the subject of this research. The result of this research showed that there are still many students’ writing that do not contain coherence and unity, they are: coherence and unity or advance criteria are 6 students, intermediate 9 students, Basic criteria are 6 students, Beginner criteria are 4. By seeing the research findings, the researcher concluded that the ability of the students in writing descriptive paragraph is still did not able to writing with coherence and unity.